Handel's Messiah rocks a joyful noise - Lockhart, Keith 1959- (Sony Music Entertainment, 2009)
A contemporary rock music adaptation of Handel's Messiah
Interpr.: J. Robert Spencer, LaChanze, Mig Ayesa ; Keith Lockhart ; with members of the Boston Pops ; and various performersVideo director/editor, Matt Hoffman ; music producer, Billy Jay Stein ; music director, Jason Howland. - Includes special features
Overture -- Comfort ye -- He'll come in glory -- He is fire -- Rejoice -- Behold the lamb of God -- He was despised -- He trusted you -- King of glory -- He is my son -- How beautiful -- Hallelujah -- A child is born
Keywords: Oratorios / Excerpts, Arranged; Rock music / 2001-2010; Christian rock music; Rock music; DVD-Video